IgG1 pan-neurofascin antibodies identify a severe yet treatable neuropathy with a high mortality. Issue 10 (16th August 2021) - Fehmi, Janev; Davies, Alexander J; Walters, Jon; Lavin, Timothy; Keh, Ryan; Rossor, Alexander M; Munteanu, Tudor; Delanty, Norman; Roberts, Rhys; Bäumer, Dirk; Lennox, Graham; Rinaldi, Simon
Abstract : Objectives: We aimed to define the clinical and serological characteristics of pan-neurofascin antibody-positive patients. Methods: We tested serum from patients with suspected immune-mediated neuropathies for antibodies directed against nodal/paranodal protein antigens using a live cell-based assay and solid-phase platform. The clinical and serological characteristics of antibody-positive and seronegative patients were then compared. Sera positive for pan-neurofascin were also tested against live myelinated human stem cell-derived sensory neurons for antibody binding. Results: Eight patients with IgG1 -subclass antibodies directed against both isoforms of the nodal/paranodal cell adhesion molecule neurofascin were identified. All developed rapidly progressive tetraplegia. Cranial nerve deficits (100% vs 26%), autonomic dysfunction (75% vs 13%) and respiratory involvement (88% vs 14%) were more common than in seronegative patients. Four patients died despite treatment with one or more modalities of standard immunotherapy (intravenous immunoglobulin, steroids and/or plasmapheresis), whereas the four patients who later went on to receive the B cell-depleting therapy rituximab then began to show progressive functional improvements within weeks, became seronegative and ultimately became functionally independent. Conclusions: IgG1 pan-neurofascin antibodies define a very severe autoimmune neuropathy. We urgently recommend trials of targeted immunotherapy for this serologically classified patient group.